Analisa Pemanfaatan Kompresor BOG K-6801 A/B pada Fasilitas LNG Hub - Fadhel Muhammad; Syafruddin Syafruddin; Ratna Sari (Jurnal Teknologi, 2023)
Boil Off Gas (BOG) is formed as a result of the evaporation of liquefied gas at atmospheric pressure as a result of the expansion of the cargo space such as a tank which can endanger the condition of the tank if it exceeds the pressure design on the tank. So, to maintain pressure in safe conditions, the BOG usually has to be burned and directed to the flare. In another word, the factory has been wasting clean gas for free. So there is a better option to use a compressor for fuel-to-plant operation. Compressor K-6801 is a centrifugal type compressor with a single casing multi-stage compressor, with a prime mover or drive in the form of an electric motor. The BOG compressor functions to compress/drain the evaporation gases (Boil Off Gas) from the LNG tank to the PLTMG and the fuel system, while the excess output from the compressor BOG will be flowed to the booster compressor to flow along with the output from the ORV to the ARBEL (Arun-Belawan) gas network. The output BOG from the LNG tank will enter the compressor suction with a temperature of -145.5 °C and a pressure of 0.00054 kg/cm2G, where it will then come out of the discharge of the BOG compressor with ambient temperature conditions of 51.6 °C and a pressure of 15.4 kg/cm2G. After manual calculations, there was a decrease in efficiency by 13% from 98% of the design data to 85%, and a decrease in efficiency through Hysys by 21% to 77%.